O sagrado em literatura infantil brasileira de 1950 1985 - Piedade, Amir Aparecido dos Santos (2006)
This work analyses the Brazilian Children s Literature in between 1950 and 1985, and has as main objective to identify in which authors whose works are still published we can find references to the Sacred, whether in poetry or prose. The methodology used was a research in publications of Children s Literature and hermeneutics from the works of the selected authors. The hypothesis is that the Sacred s marks left by the authors never should be seen like evangelization and catechesis, but like a childish and loving engagement with the Transcendent. And also, it can be used as an orientation to the new authors and to the editorial business, that there is no problem in publishing texts that contains representations, symbols or Sacred manifestations to children, on the contrary, it helps them to see the experience with the Sacred as an integral part of their formation and it can follow them, with no problems, throughout life, contributing to the individual and collective formation, and the search for understanding of great questions of humanity